Human Resource Management Strategies in the Age of 5.0 - Ruangkalapawongse, Annop; Ruangkalapawongse, Sarawan (Journal of Rattana Bundit University, 2022)
This article aims to present the perspective of management using the human resources management strategy in the 5.0 era, which is the human resources management strategy to create success in the operation and used in the strategic implementation of the human resources department in the organization for maximum effectiveness as well as to modify the competence of personnel in the organization, create new opportunities for personnel through reskill and upskill. Importantly, the personnel has access to appropriate development. Prepare to plan to deal with the organization to move forward in the uncertainty of the ever-changing world. It is the desire of the organization that wants to change the behavior of personnel in the organization as a whole, especially to find a way to create a balance within the organization with a modern form of human resource management that tends to disruption. In the 5.0 era, an intelligent society where cyber and real world seamlessly integrate information, networks, and scientific logic with social science. Because the system of working with the same skills may no longer be desirable. The results of the study found that determining strategies in human resource management by laying the foundation and restructuring the organization that is suitable must pay attention to the concept of modern work style, data driven, work predictive data analysis, application of technology in personnel management, various working skills, the culture empathizes with each other, creating work experiences that match your lifestyle and flexible working according to people for the benefit of personnel operations and benefits to the organization in the long run.